Quality of life and hospital re-admission in patients with chronic obstructive pulmonary disease. Issue 1 (January 1997) - Osman, I M; Godden, D J; Friend, J A; Legge, J S; Douglas, J G
Abstract : BACKGROUND: There is some evidence that quality of life (QOL) in patients with chronic obstructive pulmonary disease (COPD) may predict clinical outcomes and use of resources. This study examined whether QOL scores could prospectively predict re-admission for COPD or death within 12 months of an original admission, and whether QOL scores predicted home nebuliser provision. METHODS: The study was carried out in all acute medical wards of Aberdeen Royal Infirmary, Woodend and City Hospitals, Aberdeen over 12 months. A total of 377 patients admitted with an exacerbation of COPD were identified in this time, 111 of whom were not included in the study because they refused the interview or died before discharge. The remaining 266 patients completed the St George's Respiratory Questionnaire (SGRQ). Information on spirometric parameters, nebuliser provision at discharge, provision of domiciliary oxygen, and re-admission within 12 months was collected from patient notes. RESULTS: The mean age of the patients was 68 years and 53% were men. The mean (SD) forced expiratory volume in one second (FEV1) was 38.8 (18.0)% predicted and forced vital capacity (FVC) was 58.9 (23.8)% predicted. Higher (worse) scores on the SGRQ were significantly related to re-admission for COPD in the next 12 months (difference = 4.8, 95% CI 1.6 to 8.0). Patients who were re-admitted and died from COPD did not differ in SGRQ scores from those who were re-admitted and survived for more than 12 months. Re-admission was not related to sex, age, or pulmonary function. One hundred and thirty eight patients did not have a home nebuliser before admission. Of these, 14 were provided with a home nebuliser at discharge. Patients provided with nebulisers had significantly worse SGRQ scores and worse FVC. The 41 patients given domiciliary oxygen did not differ in SGRQ or spirometric parameters. Logistic regression analysis of the three SGRQ subscales (Symptom, Impact and Activity), adjusting for lung function, age and sex, showed that all three subscales were significantly related to hospital readmission and that Impact scores were related to nebuliser provision. Women did not differ from men in Symptom scores on the SGRQ but differed markedly on the Activity and Impact scales. CONCLUSIONS: It is concluded that poor scores on the SGRQ, a QOL scale which measures patient distress and coping, are associated with re-admission for COPD and use of resources such as nebulisers, independent of physiological measures of disease severity.